Gradient Lattice Structure Bio Mimicry Design Configurations for Additive Manufacturing - Seharing, Asliah; Hadi Azman, Abdul; Abdullah, Shahrum (International Journal of Engineering and Technology, 2019)
The aim of this paper is to determine design configurations of gradient lattice structures through biomimicry for lightweight additive manufactured part designs. Additive manufacturing has led to a better future in the manufacturing field. The capability to manufacture complex models is now possible through additive manufacturing. It is now possible to manufacture metallic end-user lightweight parts such as gradient lattice structures. However, the design for these lightweight gradient lattice structures is yet to be fully explored. This paper identifies and proposes the design configurations of gradient lattice structures for metallic additive manufacturing. The methodology used to propose the design configurations is through observation of cellular structures in nature, such as porous wood and bones, and through biomimicry, imitate their design through the proposal of gradient lattice structures configurations. From the analysis, key design configurations were identified and proposed to facilitate the design of gradient lattice structures. The proposed design configurations were divided into three categories, which are the pattern, relative density and progressivity. In conclusion, these findings will help designers to choose among the design variables proposed to achieve the desired functionality of the model.Â